2010
DOI: 10.3109/13651501.2010.506007
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of serum bilirubin level in schizophrenia

Abstract: Objective. Alteration of serum bilirubin level in acute episodes of psychosis in patients with schizophrenia has been reported but the pattern of this alteration is controversial. Methods. Patients diagnosed as schizophrenia (162, group S) or bipolar disorder (155, group B) entered the study. The control group consisted of 95 patients admitted to cardiac care unit who had no personal or family history of major psychiatric disorders. Pre- and post-admission levels of bilirubin were measured and compared within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Semnani et al 5 published a study in which 162 patients with schizophrenia, 155 patients with bipolar disorder (BD) type I, and 95 patients with cardiac disease had their serum levels of TB and CB measured both at admission and at discharge and after treatment. The initial mean TB level of patients with schizophrenia was in the normal range but significantly higher than that of patients with BD, and the same parameter was higher in patients with BD than patients with cardiac disease.…”
Section: High Levels Of Ucb In Humans With Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Semnani et al 5 published a study in which 162 patients with schizophrenia, 155 patients with bipolar disorder (BD) type I, and 95 patients with cardiac disease had their serum levels of TB and CB measured both at admission and at discharge and after treatment. The initial mean TB level of patients with schizophrenia was in the normal range but significantly higher than that of patients with BD, and the same parameter was higher in patients with BD than patients with cardiac disease.…”
Section: High Levels Of Ucb In Humans With Schizophreniamentioning
confidence: 99%
“…Some studies have found a possible correlation between UCB levels and an increased incidence of schizophrenia. [4][5][6][7] UCB levels may have both direct and indirect toxic effects on the central nervous system (CNS), 8 with animal models (Gunn rat) presenting schizophrenia-like behavior. 9 Therefore, measurement of serum concentrations of UCB has been proposed as a possible biomarker for the management of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Berbeda dengan hasil tersebut, temuan lain menunjukkan bahwa peningkatan bilirubin berkorelasi dengan general symptom dan positive symptom. 4,5,8 Pada penelitian ini, meskipun kadar bilirubin umumnya masih dalam batas normal, kadar UCB relatif lebih tinggi pada pasien psikotik, utamanya yang didiagnosis sebagai skizofrenia, dibandingkan dengan kontrol.…”
Section: Pembahasanunclassified
“…[1][2][3] It seems that unconjugated bilirubin (UCB), through its neurotoxic effect, 4 may be particularly interesting as a biomarker candidate in the distinction between schizophrenia and bipolar disorder. 5,6 We present a patient with atypical psychosis, high UCB levels, and electroencephalographic (EEG) changes.…”
Section: Mitsuda Psychosis and Holodysphrenia Revisitedmentioning
confidence: 99%